2022
DOI: 10.3390/app122211734
|View full text |Cite
|
Sign up to set email alerts
|

Normal-Weight Concrete with Improved Stress–Strain Characteristics Reinforced with Dispersed Coconut Fibers

Abstract: According to the sustainable development concept, it is necessary to solve the issue of replacing fiber from synthetic materials with natural, environmentally friendly, and cheap-to-manufacture renewable resources and agricultural waste. Concrete is the primary material for which fibers are intended. Therefore, the use of vegetable waste in concrete is an essential and urgent task. Coconut fiber has attracted attention in this matter, which is a by-product of the processing of coconuts and makes it relevant. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 54 publications
1
26
0
2
Order By: Relevance
“…Most researchers explored natural bers with lengths ranging from 10 to 60 mm in research and development of ber cement products largely focused on mechanical characteristics (Kriker et al 2005). Shcherban' et al (Shcherban' et al 2022) studied the improvement of mechanical characteristics in normal weight concrete by varying the proportion of coconut ber from 0-2.5% with an increment of 0.25 wt.%. The obtained results revealed that the most appropriate proportion of coconut bers was found to be 1.75% with compressive strength of 40-50 MPa and axial tensile strength of 3-4.3 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers explored natural bers with lengths ranging from 10 to 60 mm in research and development of ber cement products largely focused on mechanical characteristics (Kriker et al 2005). Shcherban' et al (Shcherban' et al 2022) studied the improvement of mechanical characteristics in normal weight concrete by varying the proportion of coconut ber from 0-2.5% with an increment of 0.25 wt.%. The obtained results revealed that the most appropriate proportion of coconut bers was found to be 1.75% with compressive strength of 40-50 MPa and axial tensile strength of 3-4.3 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…The study presented in this article develops the ideas of the concept of sustainable environmentally friendly concrete, which implies the partial and complete replacement of the mineral components of concrete with natural and rapidly renewable analogues. Replacing large-mineral aggregate with walnut shells will partially eliminate complex mechanized and energy-intensive production processes associated with high greenhouse-gas emissions [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. At the same time, it is important to find a balance between the strength and density of the resulting composite, so that a decrease in the SC of the material is accompanied by a commensurate decrease in the density of the material.…”
Section: Introductionmentioning
confidence: 99%
“…A composite material is a system of materials made up of a matrix and reinforcing fillers. These two components work together to produce unique features neither could have on their own [ 6 , 7 , 8 , 9 ]. In polymer matrix composites, fibers with fine diameters (carbon, glass, boron, aramid, Kevlar, and light carbon-based fibers) are used as the matrix and polymer (e.g., epoxy, polyester, urethane) as the binding agent.…”
Section: Introductionmentioning
confidence: 99%